Student Teams Achievement Division Technique and Group Investigation Technique Through Lesson Study Enhancing Students Learning Outcomes - Candradewi, W M V Cahyanti; Dharsana, I Ketut; Tegeh, I Made (Universitas Pendidikan Ganesha, 2020)
The finding of learning outcomes is low in this study; therefore, this study aims to determine the effectiveness of constructivism theory with the Student Teams Achievement Division technique and Group Investigation techniques through Lesson Study related to thematic learning in fifth-grade elementary school. This research is a quasi-experimental research design with Randomized Control Trials (RCTs). The population of this research is 26 students in VB class. 13 VB class students as an experimental group and 13 VB class students as a control group. Obtaining data was collected with 30 multiple choice test instruments. Data collected were analyzed using descriptive statistics and an Independent Sample t-test. Based on the results of the study after testing the hypothesis using SPSS 25.00 for Windows in the decision table the value of Sig. (2-tailed) = 0.005 which means the significance value (2-tailed) <0.05 (0.005 <0.05), then H0 is rejected and H1 = accepted. This means that the results of the study indicate that there is a significant influence on the experimental group taught by the Student Teams Achievement Division technique and the Group Investigation technique through lesson study with a control group that the teacher learns as usual on student learning outcomes. Thus, it can be concluded that the theory of constructivism with the Student Teams Achievement Division technique and Group Investigation lesson study techniques effectively improve the thematic learning outcomes of VB grade students.